(untitled) - Grant, Linda (New York, NY, 2001)
Offering a lively and communicative approach for increasing pronunciation and speaking skills, Well Said Intro provides beginning to mid-intermediate students with the pronunciation and speaking tools they need to communicate in social, academic, and professional settings.
Keywords: Tiếng Anh,English language; Phát âm,Pronunciation